Determinan Firm Value Berdasarkan Good Corporate Governance, Investment Opportunity Set, dan Firm Size - Adinda Eka Bunga Lestari; Jojok Dwiridotjahjono (Jurnal Riset Akuntansi, 2026)
This study aims to examine the effect of Good Corporate Governance, Investment Opportunity Set, and Firm Size on Firm Value in banking companies listed in the LQ45 index during the 2020–2025 period. The research employed a quantitative approach using secondary data obtained from the annual reports and financial statements of selected companies. The sampling technique used purposive sampling based on predetermined criteria, resulting in banking companies that consistently met the research requirements during the observation period. Data analysis was conducted using multiple linear regression with the assistance of EViews software. The findings indicate that all independent variables simultaneously have a significant effect on Firm Value. Partially, the audit committee and Investment Opportunity Set significantly affect Firm Value, while independent commissioners and Firm Size do not show a significant effect. These results suggest that effective supervisory mechanisms and investment growth opportunities are important considerations for investors in evaluating banking companies and making investment decisions.